Understanding Ethanol Tolerance Mechanism in Saccharomyces cerevisiae to Enhance the Bioethanol Production: Current and Future Prospects - Jhariya, Upasana; Dafale, Nishant A.; Srivastava, Shweta; Bhende, Rahul S.; Kapley, Atya; Purohit, Hemant J. (Bioenergy research, 2021)
The commercial production of bioethanol from lignocellulosic biomass is challenged by the repression of cell growth and compromised fermentation conditions. However, employing Saccharomyces cerevisiae is an economically feasible process resulting in the effective conversion of fermentable sugars to bioethanol. S. cerevisiae’s high productive feature is contributed by robust alcohol dehydrogenase and the ability to tolerate various stresses during the fermentation process. The present review employs various bioinformatics pipeline to assess the structural insights of ADH and interaction among the tolerance genes. Docking of S. cerevisiae’s ADH interaction shows the high binding affinity of − 2.81 Kcal/mol with acetaldehyde contributed by four zinc fingers. In inhibitor tolerance capacity of S. cerevisiae was explored. The STRING platform sheds light on the mechanism and interaction of ASR1 and other stress-responsive elements playing a pivotal role in ethanol tolerance. The stress-responsive genes such as HSPs and MSN2/4 provide balanced physiology under various stress conditions. The present review unravels the complex mechanism behind the inhibitor and ethanol tolerance, directing to several bottlenecks for the improvisation of S. cerevisiae’s performance.